Trzęsienie ziemi jako źródło polisensorycznego odbioru krajobrazu w "Rombo" Esther Kinsky - Feliksik, Paulina (Przestrzenie Teorii, 2025)
The article presents an analysis of Esther Kinsky’s novel Rombo in terms of sensory geography and research on the relationship between the sense of hearing and the landscape. The aim was to show that the earthquake enabled a consciously polysensory experience of the landscape of the valley below Monte Canin, and therefore its perception both before and after the 1976 events in the province of Udine in northern Italy was taken into account. Given the nature of the event and its aftermath, it was also important to look at the haptics present in the literary characters’ relationship to the landscape. The analysis underscores the inextricable link between the various senses (primarily hearing, touch and sight) and the experience of the landscape.